Towards an alternative representation of indoor acoustic environment - Bailhache Simon; Maillard Julien; Guigou-Carter Catherine (Acta Acustica, 2022)
The purpose of this investigation is to propose an alternative indoor sound spectrum based on objective and verifiable data, representative for an average household in Europe. It is obtained from the energetic sum of the emission spectra of sound sources commonly found in residential buildings, each weighted by its estimated occurrence time. Such a spectrum could then be used to evaluate airborne sound transmission performance.